Arabidopsis WRKY50 and TGA Transcription Factors Synergistically Activate Expression of PR1 - Hussain, Rana M. F.; Sheikh, Arsheed H.; Haider, Imran; Quareshy, Mussa; Linthorst, Huub J. M. (Frontiers in Plant Science, 2018)
Arabidopsis PR1 is a salicylic acid (SA) inducible marker gene for systemic acquired resistance (SAR). However, the regulation of PR1 in plants is poorly understood. In this study, we showed that AtWRKY50 transcription factor binds to two promoter elements of PR1 via its DNA binding domain. Interestingly, the DNA-binding sites for AtWRKY50 deviate significantly from the consensus WRKY binding W-box. The binding sites are located in close proximity to the binding sites for TGA transcription factors. Transactivation experiments in Arabidopsis protoplasts derived from wild type, npr1-1 and tga256 mutant plants indicated that AtWRKY50 alone was able to induce expression of a PR1::β-glucuronidase (GUS) reporter gene, independent of TGAs or NPR1. However, co-expression of TGA2 or TGA5 with AtWRKY50 synergistically enhanced expression to high levels. Yeast-2-hybrid assays and bimolecular fluorescence complementation (BiFC) experiments revealed that AtWRKY50 could interact with TGA2 and TGA5. Using electrophoretic mobility shift assays (EMSA) it was established that AtWRKY50 and TGA2 or TGA5 simultaneously bind to the PR1 promoter. Taken together, these results support a role for AtWRKY50 in SA-induced expression of PR1.